(untitled) (Journal of Engineering, 2017)
Numerical study has been conducted to investigate the thermal performance enhancement of flat plate solar water collector by integrating the solar collector with metal foam blocks.The flow is assumed to be steady, incompressible and two dimensional in an inclined channel. The channel is provided with eight foam blocks manufactured form copper. The Brinkman-Forchheimer extended Darcy model is utilized to simulate the flow in the porous medium and the Navier-Stokes equation in the fluid region. The energy equation is used with local thermal equilibrium (LTE) assumption to simulate the thermofield inside the porous medium. The current investigation covers a range of solar radiation intensity at 09:00 AM, 12:00 PM, and 04:00 PM on the 8th of July 2016 under Iraq climate conditions, and a range of Reynolds number of (207<Re<625). The results show that the insertion of metal foam blocks caused a reduction in the absorber plate temperature and the possible enhancement in the heat transfer coefficient is more than 80% and as a result, the collector exhaust temperature will increase.